Analisis Pemasaran Beras di Desa Ameroro Kecamatan Uepai Kabupaten Konawe - Andriani, Meti; Salam, Idrus; Yusria, Wa Ode (Department of Agribusiness, Halu Oleo University, 2018)
This study aims to know: 1. The pattern of rice distribution in the village Ameroro District Uepai Regency Konawe and 2. Efficiency marketing rice in the village Ameroro District Uepai Regency Konawe. This study carried in January – March 2017. Determination of the sample is done by the method snowball sampling with sample 7 respondents. The result showed that the pattern of rice distribution in the village Ameroro consists of four distribution patterns, namely: I. dealers gatherers village –> traders retailers Uepai –> consumers; II. dealers gatherers village –> traders retailers Wawotobi –> consumers; III. dealers gatherers village –> traders retailers city Kendari –> consumer; IV. Level efficiency marketing of each distribution patterns rice, namely: on the distribution patterns I for 86,56%. Distribution patterns II for 86,56%. On the distribution patterns, III of 83,92% and on the distribution patterns IV level efficiency marketing rice is 89.08%.